Answer with Step-by-step explanation:
The given differential equation is
![(2x+5y)dx+(5x-4y)dy=0](https://img.qammunity.org/2020/formulas/mathematics/college/zelznan67fvnnal8tgvkqfhjywepj5hyv9.png)
Now the above differential equation can be re-written as
![P(x,y)dx+Q(x,y)dy=0](https://img.qammunity.org/2020/formulas/mathematics/college/4x1ks2mj20995wbbcjwd8ff0bnlpw1m9rd.png)
Checking for exactness we should have
![(\partial P)/(\partial y)=(\partial Q)/(\partial x)](https://img.qammunity.org/2020/formulas/mathematics/college/yvbyn3osnfhdwl082d0osr7os6fn1r95bh.png)
![(\partial P)/(\partial y)=(\partial (2x+5y))/(\partial y)=5](https://img.qammunity.org/2020/formulas/mathematics/college/dzm58vwbuht28xqx2vln4rpy7zbfil1m8l.png)
![(\partial Q)/(\partial x)=(\partial (5x-4y))/(\partial x)=5](https://img.qammunity.org/2020/formulas/mathematics/college/tlx9ptu2to4ovj4yfx2zn4wx851u9m3pk6.png)
As we see that the 2 values are equal thus we conclude that the given differential equation is exact
The solution of exact differential equation is given by
![u(x,y)=\int P(x,y)dx+\phi(y)\\\\u(x,y)=\int (2x+5y)dx+\phi (y)\\\\u(x,y)=x^2+5xy+\phi (y)](https://img.qammunity.org/2020/formulas/mathematics/college/wvhgqo3r85gr17qerjo1uev2bkeqckz86q.png)
The value of
can be obtained by differentiating u(x,y) partially with respect to 'y' and equating the result with P(x,y)
![(\partial u)/(\partial y)=(\partial (x^2+5xy+\phi (y))))/(\partial y)=Q(x,y))\\\\5y+\phi '(y)=(5x-4y)\\\\\phi '(y)=5x-9y\\\\\int\phi '(y)\partial y=\int (5x-9y)\partial y\\\\\phi (y)=5xy-(9y^2)/(2)\\\\\therefore u(x,y)=x^2+10xy-(9y^2)/(2)+c](https://img.qammunity.org/2020/formulas/mathematics/college/6abrqr5a6hhsrcjslpedqh1p5hi779ek42.png)